The efficacy of azithromycin combined with seven types of Chinese medicine injections in the treatment of Mycoplasma pneumoniae pneumonia in children: a systematic review and Bayesian network meta-analysis - Huang, Xinggui; Tao, Sian; Liu, Chenhao; Sun, Xiaoluo; Hao, Yule; Ma, Yuqi; Liu, Yi; Liu, Jibin (Frontiers in Pharmacology, 2024)
Mycoplasma pneumoniae pneumonia (MPP) is the predominant community-acquired pneumonia (CAP) in children aged 5 years or older. In recent decades, the annual increase in drug resistance rates of macrolide antibiotics, particularly azithromycin (AZ), has led to complex clinical treatment strategies and substantial healthcare costs associated with MPP. Chinese medicine injections (CMIs), recognized as an effective supplementary therapy, are acknowledged by clinicians in China. It is necessary to explore the efficacy of azithromycin in combination with CMIs. Methods Randomized controlled trials (RCTs) evaluating azithromycin in combination with seven types of CMIs for MPP in children were identified based on inclusion criteria and assessed using the revised Cochrane risk of bias tool (RoB 2.0). R 4.3.1 and STATA 15.0 were employed to generate ranking probabilities and perform network meta-analysis. Competing interventions were ranked using the surface under the cumulative ranking (SUCRA) probabilities. Results A comprehensive analysis was performed on 155 RCTs involving 15,014 patients and 8 therapeutic strategies within this Bayesian network meta-analysis (BNMA). The results indicated that AZ combined with seven types of CMIs was more effective than azithromycin alone in overall outcomes. Notably, azithromycin combined with Chuanhuning injection (AZ + CHN) achieved the highest ranking in improving the clinical effectiveness rate (SUCRA, 80.89%); regarding secondary outcome measures, azithromycin combined with Yanhuning injection (AZ + YHN) had the highest probability of improving four different outcomes: disappearance time of cough (SUCRA, 80.01%), disappearance time of pulmonary rale (SUCRA, 87.77%), disappearance time of fever (SUCRA, 95.70%), and disappearance time of pulmonary shadows in X-ray (SUCRA, 97.34%); furthermore, azithromycin combined with Qingkailing injection (AZ + QKL) was more likely to reduce average hospitalization time (SUCRA, 94.60%). Conclusion This study highlights the potential benefits of seven types of Chinese medicine injections as adjunctive therapy for Mycoplasma pneumoniae pneumonia in children. However, further support and validation of these findings are needed through high-quality randomized controlled trials with larger sample sizes and double-blind designs. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/#recordDetails/.